Invisibilizar a las víctimas, ocultar las violencias: victimización sexual y estadística penal = Invisibilizing victims, hiding violence : sexual victimization and criminal statistics - Rodríguez Luna, Ricardo (Oñati Socio-Legal Series, 2021)
Criminal justice statistics that collect specific information on the victim are relatively recent, a good example in this regard is the Censo Nacional de Impartición de Justicia Estatal. This research studies the data from this census, although the focus is on the victims of rape. The results confirm that women, particularly girls and young women, are the main victims of this crime. In addition, the findings show gaps in the information that allow questioning its consistency and reliability. The conclusions, therefore, suggest that the over-representation of women in statistics is only a reflection of a much larger problem, but its dimensions are blurred and invisible due to the same inconsistencies in the census data.